Epidemiology of clinically isolated methicillin-resistant Staphylococcus aureus (MRSA) and its susceptibility to linezolid and vancomycin in Egypt: a systematic review with meta-analysis - Azzam, Ahmed; Khaled, Heba; Mosa, Maha; Refaey, Neveen; AlSaifi, Mohammed; Elsisi, Sarah; Elagezy, Fatma Khaled; Mohsen, May (BMC infectious diseases, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major nosocomial pathogen that causes severe morbidity and mortality worldwide. For the establishment of national strategies to combat MRSA infection in each country, accurate and current statistics characterizing the epidemiology of MRSA are essential. The purpose of this study was to determine the prevalence of MRSA among Staphylococcus aureus clinical isolates in Egypt. In addition, we aimed to compare different diagnostic methods for MRSA and determine the pooled resistance rate of linezolid and vancomycin to MRSA. To address this knowledge gap, we conducted a systematic review with meta-analysis. A comprehensive literature search from inception to October 2022 of the following databases was performed: MEDLINE [PubMed], Scopus, Google Scholar, and Web of Science. The review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) Statement. Based on the random effects model, results were reported as proportions with a 95% confidence interval (CI). Analyses of the subgroups were conducted. A sensitivity analysis was conducted to test the robustness of the results. A total of sixty-four (64) studies were included in the present meta-analysis, with a total sample size of 7171 subjects. The overall prevalence of MRSA was 63% [95% CI: 55-70]. Fifteen (15) studies used both PCR and cefoxitin disc diffusion for MRSA detection, with a pooled prevalence rate of 67% [95% CI: 54-79] and 67% [95% CI: 55-80], respectively. While nine (9) studies used both PCR and Oxacillin disc diffusion for MRSA detection, the pooled prevalences were 60% [95% CI: 45-75] and 64% [95% CI: 43-84], respectively. Furthermore, MRSA appeared to be less resistant to linezolid than vancomycin, with a pooled resistance rate of 5% [95% CI: 2-8] to linezolid and 9% [95% CI: 6-12] to vancomycin, respectively. Our review highlights Egypt's high MRSA prevalence. The cefoxitin disc diffusion test results were found to be consistent with PCR identification of the mecA gene. A prohibition on antibiotic self-medication and efforts to educate healthcare workers and patients about the proper use of antimicrobials may be required to prevent further increases.